2007
DOI: 10.1007/s11182-008-9002-9
|View full text |Cite
|
Sign up to set email alerts
|

Spall fracture of coarse-grained and ultrafine-grained aluminum under nanosecond relativistic high-current electron beam

Abstract: The results of investigations of fracture behavior in coarse-grained and ultrafine-grained aluminum under the action of a nanosecond relativistic high-current electron beam in a SINUS-7 accelerator and under conditions of quasi-static tensile loading are reported. It is shown that for both types of deformation, irrespective of the grain size, the fracture is ductile both in deformation and structural features. Based on the examination of the fracture surface, it is found out that under quasi-static loading dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…An answer to this question is also critical in terms of revealing the mechanism of spalling fracture of ultrafine-grained metals and alloys under high-density energy flows, and constructing its structural model. This work is an extension of the studies reported in [11,12] and provides a comparative analysis of the microstructure evolution and the mechanism of spalling fracture of a heterophase Al -5.5% Mg -2.2% Li -0.12% Zr (wt.%) alloy in its coarse-and ultra-fine-grained states under the action of a nanosecond relativistic high-current electron beam.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…An answer to this question is also critical in terms of revealing the mechanism of spalling fracture of ultrafine-grained metals and alloys under high-density energy flows, and constructing its structural model. This work is an extension of the studies reported in [11,12] and provides a comparative analysis of the microstructure evolution and the mechanism of spalling fracture of a heterophase Al -5.5% Mg -2.2% Li -0.12% Zr (wt.%) alloy in its coarse-and ultra-fine-grained states under the action of a nanosecond relativistic high-current electron beam.…”
Section: Introductionmentioning
confidence: 87%
“…These data were obtained at the strain rates less than 1·10 -1 s -1 in the region of moderate homological temperatures. Only more recent publications report deformation behavior and fracture of ultra-fine-grained metallic materials at the strain rates 10 4 -10 6 s -1 [8][9][10][11][12]. It should be noted that along with the high-speed impact of plates the authors of these studies used shock waves generated by the exposure to high-current electron beams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the spalling fracture of metal materials, shock waves generated by high-current ion and electron beams have been used in addition to high-speed impact of plates [11][12][13][14][15][16][17][18][19]. In the present work, such investigation is performed for titanium VT1-0 with ultrafine-grained and coarse-grained structures.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest are investigations into the deformation and fracture processes developing in ultrafine-grained and nanostructured materials under pulsed and shock loading [1][2][3][4]. These investigations provide information on the fundamental strength properties of the materials.…”
mentioning
confidence: 99%